Data for RSF analysis of caribou - Courbin, Nicolas; Fortin, Daniel; Dussault, Christian; Courtois, R. (Dryad Digital Repository, 2014)
Data used to model the relative probability of occurrence of caribou in winter as a function of landscape features (Table 1). Landscape features (various land cover types and variation of elevation within a 50-m radius buffer) are provided at observed GPS locations and at random locations.